2020
DOI: 10.3390/app10051675
|View full text |Cite
|
Sign up to set email alerts
|

Factor Identification and Prediction for Teen Driver Crash Severity Using Machine Learning: A Case Study

Abstract: Crashes among young and inexperienced drives are a major safety problem in the United States, especially in an area with large rural road networks, such as West Texas. Rural roads present many unique safety concerns that are not fully explored. This study presents a complete machine leaning pipeline to find the patterns of crashes involved with teen drivers no older than 20 on rural roads in West Texas, identify factors that affect injury levels, and build four machine learning predictive models on crash sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…On the other hand, one hot encoder converts the categorical variable into a sparse binary matrix. The results of this study indicate that the combination of label encoder and XGBoost appeared to yield better accuracy and computation time [14]. Along the same line of thought, Zhang et al compared the prediction performance of two discrete choice models and four ML models to predict the injury severity in crashes at freeway diverge areas in Florida.…”
Section: Summary Of the Literature Reviewmentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, one hot encoder converts the categorical variable into a sparse binary matrix. The results of this study indicate that the combination of label encoder and XGBoost appeared to yield better accuracy and computation time [14]. Along the same line of thought, Zhang et al compared the prediction performance of two discrete choice models and four ML models to predict the injury severity in crashes at freeway diverge areas in Florida.…”
Section: Summary Of the Literature Reviewmentioning
confidence: 75%
“…To address the potential shortcoming related to missing features, the input data was expanded by adding the reactive data, specifically the driver age and vehicle age variables. As noted in the literature review, the studies have shown that driver and vehicle characteristics have a significant impact on crash occurrence and their severity outcomes [14][15][16]. Despite the critical impact of the factors described by reactive data on the crash severity outcomes, the main challenge of using the reactive data for operational crash prediction is that they are not available in real-time.…”
Section: Application Of Reactive Data In the Crash Severity Modelmentioning
confidence: 99%
“…Machine learning has recently received attention due to the emergence of big data generated by multiple sources and the availability of computational power [26]. It performs well in solving several complex and nonlinear problems [27,28] and is widely applied in the prediction of drivers' behavior and some traffic-safety-related researches [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deep learning, according to the study, improved prediction performance for both fatal and non-fatal injuries. Lin et al [ 21 ] employed four machine learning classifiers to forecast the injury severity caused by juvenile driving incidents on West Texas’ rural roadways. The speed limit, road class, and the first detrimental occurrence were the three most influential elements impacting injury severity, according to the experimental data.…”
Section: Introductionmentioning
confidence: 99%